2019
DOI: 10.1053/j.jvca.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter International Survey on the Clinical Practice of Ultra-Fast-Track Anesthesia with On-Table Extubation in Pediatric Congenital Cardiac Surgery

Abstract: The survey demonstrated that the majority of the approached pediatric cardiac anesthesiologists practice OTE regularly in pediatric cardiac surgery. Frequency of OTE and inclusion criteria vary widely. The observations made in this survey should prompt appropriately powered, randomized controlled clinical trials to examine the effect of OTE on various effectiveness and safety outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…Xu et al 21 demonstrated that ultrafast‐track anesthesia shortens extubation time, ICU stays, and hospital stays for children with congenital heart disease and does not increase sedation‐agitation scores or the incidence of adverse reactions. Akhtar et al 22 conducted an online survey to describe global practices for on‐table extubation in pediatric cardiac anesthesia in European and non‐European countries 22 . The authors concluded that fast‐track cardiac anesthesia could be safely used in pediatric patients undergoing the repair of simple atrial and VSDs, although it is feasible in complex surgical cases as well.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al 21 demonstrated that ultrafast‐track anesthesia shortens extubation time, ICU stays, and hospital stays for children with congenital heart disease and does not increase sedation‐agitation scores or the incidence of adverse reactions. Akhtar et al 22 conducted an online survey to describe global practices for on‐table extubation in pediatric cardiac anesthesia in European and non‐European countries 22 . The authors concluded that fast‐track cardiac anesthesia could be safely used in pediatric patients undergoing the repair of simple atrial and VSDs, although it is feasible in complex surgical cases as well.…”
Section: Discussionmentioning
confidence: 99%
“…Though ventilators are important tools in the armamentarium for the post-operative management of children undergoing surgery for CHD, mechanical ventilation for as short as 18 h leads to significant loss of cross-sectional area of diaphragmatic muscle fibres [30,31]. Every hour of mechanical ventilation increases the risk which gets compounded with the addition of sedatives.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multicentre international survey [30,31], from both European and non-European countries, a majority of paediatric cardiac anaesthesiologists practice OTE, safety of OTE was perceived as excellent by 70% of the respondents, and none of them had stopped OTE for safety reasons. The practice of OTE varies among institutions, depending on physician preferences, comfort of the entire team, and other logistic considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Kısa etkili ajanların kullanımı, minimal invaziv cerrahi yaklaşımlar ve normotermi biraraya geldiğinde kalp cerrahisinde masada ekstübasyon gündeme gelmiştir. Bu yaklaşım hem erişkin hem de konjenital hasta grubunda uygulama imkanı bulmuştur (19,20) . Ancak yeterli sayıda veri olmadığından tüm hasta grupları için güvenliği halen tartışmalıdır.…”
Section: Erken Ekstübasyon Yaklaşımıunclassified